2013
DOI: 10.1186/1477-7819-11-42
|View full text |Cite
|
Sign up to set email alerts
|

Video Endoscopic Inguinal Lymphadenectomy (VEIL) -a prospective critical perioperative assessment of feasibility and morbidity with points of technique in penile carcinoma

Abstract: BackgroundInguinal lymph node involvement is an important prognostic factor in penile cancer. Inguinal lymph node dissection allows staging and treatment of inguinal nodal disease. However, it causes morbidity and is associated with complications, such as lymphocele, skin loss and infection. Video Endoscopic Inguinal Lymphadenectomy (VEIL) is an endoscopic procedure, and it seems to be a new and attractive approach duplicating the standard open procedure with less morbidity. We present here a critical perioper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 25 publications
5
22
2
2
Order By: Relevance
“…Zhou et al 34 11 36.4 n.r. 0 Mean 126 (range 90e180) Abbott et al 35 13 0 15e25 7.7 245 (IQR 205e366) vs 138 (IQR 102e179) p ¼ 0.0003 Pahwa et al 36 10 0 12 0 135 (range 120e180) n.r. ¼ not reported.…”
Section: Ln Recurrence Ratementioning
confidence: 93%
See 2 more Smart Citations
“…Zhou et al 34 11 36.4 n.r. 0 Mean 126 (range 90e180) Abbott et al 35 13 0 15e25 7.7 245 (IQR 205e366) vs 138 (IQR 102e179) p ¼ 0.0003 Pahwa et al 36 10 0 12 0 135 (range 120e180) n.r. ¼ not reported.…”
Section: Ln Recurrence Ratementioning
confidence: 93%
“…29,33,37 Only one study reported data on the occurrence of post-operative lymphedema, which was detected in the 11% of cases. Hospital stay and drainage duration were extremely heterogenous, ranging from 1 to 11 days 28,29,32,34e36 and 5e28 days, 31,32,35,36 respectively. Strikingly, in two studies hospital stay after VEIL was significantly lower compared to open IL.…”
Section: Post-operative Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a group in India has reported similar experiences [12]; in ten patients, no skin-related complications were seen. Lymphocele was seen in 2/10 (20%) of patients, lymph node yield was 7-12 lymph nodes.…”
Section: Discussionmentioning
confidence: 68%
“…The saphenous vein is also not always preserved. 63 Tobias-Machado et al 64,65 reported favorable oncological and cosmetic outcomes with VEIL in a group of patients with nonpalpable ILNs. A similar number of ILNs were excised compared to the open approach and no reported recurrences or cases of disease progression were noted at a mean follow-up of 18.7 months.…”
Section: Surgical Treatment Of Pelvic Lnsmentioning
confidence: 97%